Atomistic Simulations of Twist Grain Boundary Structures in Aluminum-Magnesium Alloys - Kamaludin, Siti Sarah; Thamburaja, Prakash; Ariffin, Ahmad Kamal (International Journal of Engineering and Technology, 2018)
The structures and energy of grain boundaries (GBs) have a significant influence on the mechanical properties of polycrystalline material. Most metal exists in the polycrystalline form but most of the metal applications are in term of their alloys. In this paper, twist GBs in magnesium (Mg)-aluminum (Al) were simulated using atomic simulation to understand the structure and properties of GBs in alloy. The energy of 45 twists GBs were calculated and plotted. The results indicate that the GB energy of a low-range misorientation angle agrees with the Read-Shockley equation for dislocation model. In high angle GB, special behaviour correspond to low âˆ‘ values are observed.